Investigation of the possibility of increasing the life of dump truck frames - Muagkih I.D.; Goryunov S.V.; Udalova J.S. (Горное оборудование и электромеханика, 2025)
The article discusses the main causes of cracks in the frames of a quarry dump truck, provides statistical patterns of crack formation, which were obtained by expert survey. The results of the expert survey were processed using statistical analysis methods according to the loading capacity of dump trucks from 55 to 360 tons. Based on the analysis results, the relevance of research was determined due to the high frequency of various frame damage during regular operation of equipment in comparison with other causes of downtime of mining dump trucks. In particular, the data analysis revealed the localization of cracks, which most often occur in the area of the second crossbar. The damage values were also revealed depending on the dump truck's operating mode and its load capacity. The BelAZ 75605 model was chosen as the most typical representative of mining dump trucks for further analysis. The choice of dump truck is determined by the prospects of using mining dump trucks with higher carrying capacity due to the abolition of the fleet of mining dump trucks with lower carrying capacity. A three-dimensional model of the frame of the selected dump truck was created in order to computer simulate the loads and obtain data on the most loaded sections of the frame. The data obtained by computer modeling was analyzed, which revealed the values of frame deformation depending on the degree of loading of the dump truck (0%, 50% and 100% of full load) using finite element analysis. The dependence of the load change on the frame elements on the thickness of the lining is investigated. Ways to increase the life of frames by applying linings to problem areas of frames are proposed.